Teacher performance, attitude and classroom practices dataset collected to evaluate the Rwandan Quality Basic Education project - Nkundabakura, Pheneas; Nsengimana, Theophile; Byukusenge, Celine; Iyamuremye, Aloys; Batamuliza, Jane; Twahirwa, Jean Nepomuscene (Data in brief, 2022)
The Rwanda Quality Basic Education for Human Capital Development (RQBEHCD) project is financed by Word Bank Group through the Government of Rwanda and was embarked on in 2020. It aimed to provide the necessary support to upper primary and lower secondary school teachers and equip them with enough content knowledge, lab skills, pedagogy, and the use of technology in teaching. The dataset presented here comprises data collected from teachers selected in the ten districts of Rwanda. Data were collected in three ways: (a) teachers’ performance in mathematics and science subjects, (b) teachers' beliefs, and (c) classroom observation. Both quantitative and qualitative approaches were used to collect data. Data were collected before and after delivering Continuous Professional Development (CPD) training on Teacher Pedagogical Content Knowledge and the use of modernized tools and approaches. The data were gathered between July 2021 and June 2022, and teachers received the CPD training from August 2021 to April 2022. Teachers' performance data in mathematics and science subjects were collected from 657 lower secondary and 290 upper primary teachers using the teachers' performance achievement test, while beliefs data were collected from 691 secondary and 290 primary teachers using the attitude test. Furthermore, 659 lower secondary and 300 upper primary Mathematics and Science teachers were observed using the Kobo-toolbox-generated Classroom-Based Monitoring and Evaluation Tool (CMET). This data article explains how we created, collected, and analyzed data for the study. Thus, this dataset is presented in the form of raw and analyzed data. The presented data provide information teachers’ performance and beliefs in Mathematics and Science; it also enables researchers to reanalyze it based on the variables of interest. In addition, it provides a broad overview of the impact of CPD on teaching mathematics and Science in primary and secondary schools to policymakers, educators, researchers, and other stakeholders.